The Application of Compressive Sensing on Spectra De-noising - Mingxia Xiao; Lu Changhua; Ma Xing; Jiang Weiwei (Institute of Advanced Engineering and Science, 2013)
Through the analyzing of limitations on wavelet threshold filter de-noising, this paper applies wavelet filter based on compressed sensing to reduce the signal noise of spectral signals, and compares the two methods through experiments. The results of experiments shown that the wavelet filter based on compressed sensing can effectively reduce the signal noise of spectral signal. The de-noising effect of the method is better than that of wavelet filter. The method provides a new approach for reducing the signal noise of spectral signals. DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.3198